Influence of genetic and environmental factors on the response of Salmonella to heat on red meat - Sarjit, Amreeta (Curtin University, 2020)
Salmonella is one of the leading causes of foodborne bacterial gastroenteritis worldwide. Heating of red meat is a way to control the spread of Salmonella on it. This study investigated the survival of different Salmonella strains exposed to different types of heat treatment on red meat and in red meat juices. The genetic diversity of these strains and the physical environmental factors contributed to the survival of Salmonella during heating.